Teacher and Students’ Perceptions of Reading a Graphic Novel using the Multiliteracies Approach in an ESL Classroom (Malaysian Journal of Learning and Instruction, 2015)
Purpose â€“ This article reports on the practical application of Learning Elements advocated by the multiliteracies approach to classroom practice. Its ideas are grounded in the multiliteracies pedagogical principles of teaching and learning that address issues on literacy and learning in todayâ€™s globalised world. The main objective of this study was to analyse the perceptions of one ESL teacher and 24 students in reading a graphic novel using the multiliteracies approach in an ESL classroom. Methodology â€“ The study involved the collection of qualitative data which was derived from focus group interviews and a journal writing activity. These instruments aimed to get feedback from the ESL teacher and students about their perceptions of reading a graphic novel using the multiliteracies approach in the reading classroom. The materials used for the focus group interviews and the journal writing activity. The data from the focus group interviews were analysed by using thematic analysis. Meanwhile, the data from the teacher journal entries were subjected to a micro analysis approach using the content analysis method. Findings â€“ The findings showed that the students perceived the use of the graphic novel and the multiliteracies approach in their reading class positively because they felt that the lessons were engaging, enjoyable and interesting. This supported the views of the ESL teacher who advocated the inclusion of multimodal pedagogical practices in the learning context to promote positive outcomes. Significance â€“ This study would benefit ESL students in terms of enjoyment in reading. Firstly, reading a graphic novel can tap into studentsâ€™ interest and can motivate them to read and write. Additionally, it would also motivate students to learn collaboratively with their peers. The fi ndings of the study offer ESL teachers and researchers valuable insights of reading a graphic novel using the multiliteracies approach in reading classrooms, as well as planning effective lessons and integrating technology, in an effort to motivate students to read in English.